A crush on small fungi: An efficient and quick method for obtaining DNA from minute ascomycetes. Issue 1 (21st August 2017) - Sundberg, Henrik; Ekman, Stefan; Kruys, Åsa
Abstract: We have developed a reliable technique for extracting DNA from single microscopic fungal thalli, including efficient cell disruption and transfer of cell content for subsequent polymerase chain reaction (PCR). The technique was primarily developed for members of the ascomycete order Laboulbeniales, which are minute fungi with tough cell walls that are exceedingly difficult to disrupt with standard extraction techniques. Our method makes routine amplification of DNA from single thalli possible, even from small species or poorly developed individuals. DNA release is accomplished in an entirely mechanical manner using an arbor press fitted with custom‐made components. This approach has eliminated additional treatment such as laborious freeze‐thaw cycles, enzymes, or lysing agents. The overall PCR success rate of 89% is comparable to or better than alternative protocols that make use of substantially larger amounts of fungal tissue. From 97% of the successful PCRs a total of 156 sequences from four gene regions were produced. Being able to restrict DNA extractions to a single thallus is critical to all genetic studies requiring data at the level of individual, e.g. population genetics. As all researchers working with minute uncultivable organisms in many respects face the same problems (effective handling of the material, small quantities of DNA etc.), the methodology described here has a potential to be widely applicable. Necessary custom‐made components can be manufactured at fairly low cost by any precision‐tool workshop using our detail drawings.